Ekspresi Emosi (EE) dan Gejala Yang Muncul Pada Pasien Gagal Jantung - Puji Laksmini; Sri Rahayu; Mei Feng Lin; Chlara Yunita Prabawati; Bagus Sulistyo Budhi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Introduction : Heart failure is the final stage of all heart disease, and the number of morbidity and mortality increasing by the time. The signs and symptoms experienced by patients are influenced by various factors. Expressed emotion (EE) predicted the survival of heart disease in a prior study but the relationship has not yet verified. Objective: To describe the expressed emotion (EE), symptoms and its correlation between these two variables in patients with heart failure. Methods: A quantitative, cross sectional study design with structuralized questionnaires were used. Forty patients with heart failure are participated in this current study. Results: No signifcant correlation between expressed emotion (EE) and heart-failure symptoms was reported (p-value = 0.377) from the viewpoints of patients in this preliminary study. Conclusion: The relationship between EE and symptom of heart failure will be validated with a large scale and dyadic analysis approach in the future study.